Theories of Delinquency and Deviance Applied to Consumption - Sue L. T. McGregor (Australasian Accounting, Business and Finance Journal, 2022)
As aspects of ethical and moral consumption, this paper is concerned with gaining deeper insights into how people could possibly react to being judged and then labeled delinquent and deviant consumers (i.e., falling short of or neglecting to fulfill their duty to others, other species, and the Earth). To that end, theories of delinquency (rational choice, strain, anomie, social processes, subculture, and differential opportunity) and Henry and Eaton’s six degrees of deviance approach were employed to conceptualize this phenomenon. Each theory and degree of deviance is explained and then paired with a consumer example to illustrate its relevance in offering insights into people’s possible reactions to being judged and labelled delinquent and deviant consumers. Future researchers are encouraged to operationalize the ideas contained herein to see if they have empirical and theoretical merit.
Keywords: consumer behaviour; degrees of deviance; moral and ethical consumption; neutralization theory; theories of delinquency